Disease progression to chronic migraine: onset of symptoms of headaches, anxiety and mood disorders - Mercante, Juliane P. P.; Peres, Mario F. P.; Bernik, Marcio A.; Corchs, Felipe; Guendler, Vera Z.; Zukerman, Eliova (Headache Medicine, 2011)
Background: Psychiatric conditions, mostly anxiety and mood disorders, are common in patients with chronic migraine. There has recently been extensive debate on migraine progression, but little is known about the role of psychiatric disorders in this respect. Objective: In order to evaluate the role of psychiatric disorders in migraine progression, we analyzed the temporal profile of migraine, mood and anxiety disorders, and years since onset of symptoms in chronic migraine (CM) patients. Methods: Fifty CM patients diagnosed according to the International Headache Society (2004) criteria were interviewed and diagnosed for mental disorders using the Structured Clinical Interview for DSM-IV (SCID-I/P). Results: Anxiety disorders preceded the onset of episodic migraine, which was followed by depression and daily headaches. Conclusions: Psychiatric comorbidity evaluation in chronic migraine may lead to better patient management and clinical outcomes. Patients with a history of anxiety, episodic migraine, and depression may be at risk of developing CM. Early treatment of anxiety, mood disorders, and episodic migraine may prevent disease progression to CM.